The Integration of Tambourine Art as an Islamic Cultural Heritage in the Formation of Student Character at SMP Ma'arif 9 Seputih Banyak - Hidayat, Arif; Q, Ikhwan Aziz; Wijaya, Adi (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
Tambourine art is one of the Islamic cultural heritages which has educational and moral value for students. This art not only functions as entertainment, but also as an effective means of preaching in conveying moral and religious values. This research aims to analyze the role of tambourine art in forming the character of students at SMP Ma'arif 9 Seputih Banyak. Identify the problem in this journal, namely; (1) lack of integration of character education in learning, (2) lack of use of tambourine art as a medium for character education, (3) lack of attention to traditional Islamic arts, (4) the need for further study on the integration of tambourine art in character education. The method used in this research is qualitative with a descriptive approach. Data was collected through direct observation, interviews with tambourine art teachers, as well as documentation of extracurricular activities. Data analysis was carried out by identifying character patterns that developed through tambourine art extracurricular activities. The integration process is carried out through three main stages, namely; habituation, internalization of values, application of values. The research results show that the integration of tambourine art in extracurricular activities and learning is able to instill religious values, discipline, cooperation and responsibility in students. Thus, tambourine art is not only a cultural heritage, but also an effective medium in forming students' character. Tambourine art can be used as an effective educational tool in forming the character of students who are noble, cultured and have a high social spirit. In addition, with proper integration, tambourine art can become an instrument that not only preserves Islamic cultural heritage but also strengthens students' character in everyday life.